1999
DOI: 10.1136/hrt.82.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic performance of aortic pericardial bioprostheses and bileaflet prostheses at rest and during exercise: implications for the surgical management of patients with small aortic roots

Abstract: Objective-To determine the haemodynamic behaviour, at rest and during exercise, of aortic valve pericardial bioprostheses and diVerent sizes of bileaflet prosthesis. Design-Observational study. Setting-Tertiary medical centre. Patients and interventions-74 patients (33 women, 41 men; mean age 64 years) in whom 40 pericardial bioprostheses and 34 bileaflet prostheses sized 19, 21, or 23 mm had been implanted to replace aortic valves. Main outcome measures-Doppler echocardiography at rest and at peak exercise, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Second, because the stented prosthesis has its own annulus, the effective orifice area after the implantation is actually smaller than that of a normal native valve. Factors that may predict PPM preoperatively are as follows: larger body surface area, high body mass index, older age, smaller prosthesis size, and valvular stenosis as the predominant lesion before the operation [11]- [13]. Patient-prosthesis mismatch occurs more frequently in patients with stenotic native valves and in older patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, because the stented prosthesis has its own annulus, the effective orifice area after the implantation is actually smaller than that of a normal native valve. Factors that may predict PPM preoperatively are as follows: larger body surface area, high body mass index, older age, smaller prosthesis size, and valvular stenosis as the predominant lesion before the operation [11]- [13]. Patient-prosthesis mismatch occurs more frequently in patients with stenotic native valves and in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…This subsequently provides a clinical recovery and prolongs the life expectancy. In contrary, small prostheses may be threatening in especially early and late periods of life and during exercise by creating an obstruction through the left ventricle outlet [11]- [16]. It was demonstrated that both prosthetic and bioprosthetic valves are narrower than the natural valves, and although function normally, they may lead to some degree of a gradient [17] [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, a significant exercise increment of i-EOA was found in the MVRm, challenging the generally assumption which assume, in the aortic mechanical valves, an on/off phenomenon. 31 Many reasons, such as the type of effort or the method used for calculating the valve area, have been advocate, to explain this finding. 31 However, an on/off phenomenon cannot be translated to the mitral prostheses, in which the mechanism of valve opening is a complex interaction between left atrium and LV.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…31 Many reasons, such as the type of effort or the method used for calculating the valve area, have been advocate, to explain this finding. 31 However, an on/off phenomenon cannot be translated to the mitral prostheses, in which the mechanism of valve opening is a complex interaction between left atrium and LV. Hobson et al 16 reported a significant dobutamine stress increase of the EOA.…”
Section: Clinical Outcomesmentioning
confidence: 99%